Divergent Role for STAT5 in the Adaptive Responses of Natural Killer Cells - Wiedemann, Gabriela M.; Grassmann, Simon; Lau, Colleen M.; Rapp, Moritz; Villarino, Alejandro V.; Friedrich, Christin; Gasteiger, Georg; O'Shea, John J.; Sun, Joseph C. (Cell Reports, 2020)
Wiedemann et al. demonstrate that Stat5a and Stat5b are induced by IL-12 and STAT4 signaling in NK cells following MCMV infection. They further provide evidence that the cytokines IL-2 and IL-15 upstream of STAT5 differentially promote the early and late stages of the adaptive NK cell response to MCMV infection.
CRIS-Team Scopus Importer:2023-03-23
Keywords: clonal expansion; IL-15; IL-2; MCMV; memory; NK cell; STAT5